Improving thermal hysteresis activity of antifreeze protein from recombinant Pichia pastoris by removal of N-glycosylation. Issue 3 (16th March 2017) - Kim, Eun Jae; Lee, Jun Hyuck; Lee, Sung Gu; Han, Se Jong
ABSTRACT: To survive in a subzero environment, polar organisms produce ice-binding proteins (IBPs). These IBPs prevent the formation of large intracellular ice crystals, which may be fatal to the organism. Recently, a recombinant FfIBP (an IBP from Flavobacterium frigoris PS1) was cloned and produced in Pichia pastoris using fed-batch fermentation with methanol feeding. In this study, we demonstrate that FfIBP produced by P. pastoris has a glycosylation site, which diminishes the thermal hysteresis activity of FfIBP. The FfIBP expressed by P. pastoris exhibited a doublet on SDS-PAGE. The results of a glycosidase reaction suggested that FfIBP possesses complex N-linked oligosaccharides. These results indicate that the residues of the glycosylated site could disturb the binding of FfIBP to ice molecules. The findings of this study could be utilized to produce highly active antifreeze proteins on a large scale.